The antimicrobial potential of traditional remedies of Indigenous Peoples from Canada against MRSA planktonic and biofilm bacteria in wound-infection mimetic conditions - Rieger, Colin D.; Soliman, Ahmed M.; Kaplia, Kateryna; Ghosh, Nilrup; Lopez, Alexa Cervantes; Venkatesan, Surya Arcot; Flores, Abraham Gildaro Guevara; Belin, Jose Antonio Filiol; Allen, Florence; Reynolds, Margaret; McKenna, Betty; Lavallee, Harold; et al. (Cold Spring Harbor Laboratory, 2024)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) is the leading cause of wound infections, often progressing into serious invasive bloodstream infections. MRSA disproportionately affects Indigenous peoples in Canada with higher rates of skin and wound infections, an example of persistent gaps in health outcomes between Indigenous and non-Indigenous peoples precipitated by the legacy of colonialism. Conversely, Indigenous peoples have long used natural remedies for infections and other diseases; however, their knowledge was rarely considered for modern medicine. The stagnant antibiotic discovery pipeline and alarming rise of resistance to current antibiotics prompted us to turn to Indigenous medicine as an untapped source of antimicrobials. As such, we collected and prepared 85 extracts of medicinal plants of value to Indigenous Peoples spanning the Canadian Prairies. We explored the antimicrobial potential of these extracts against MRSA under wound infection-mimetic conditions compared to culture media typically used to study bacterial antibiotic responses and biofilms but not adequately representative of infection sites. We identified extracts with MRSA growth inhibitory [e.g., bergamot, dock, gaillardia, and dandelion extracts] and biofilm prevention and eradication [e.g., gumweed extracts] activities. Extracts, including those of chokecherry, hoary puccoon, and Northern bedstraw, were only active under wound infection-mimetic conditions, highlighting the relevance of antibiotic discovery under host-relevant conditions. Testing growth inhibitory extracts against an S. aureus cross-resistance platform suggested that they act through mechanisms likely distinct from known antibiotic classes. Together, through an interdisciplinary partnership leveraging Western approaches and traditional Indigenous knowledge, we identified plant extracts with promising antimicrobial potential for drug-resistant MRSA wound infections.